ANALISIS KINERJA KEUANGAN PEMERINTAH PROVINSI SUMATERA SELATAN - VANADHIA RAHMATIKA WELLYAN; EVA NOVARIA; LISDIANA LISDIANA (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2023)
This research analyzes financial performance and management in South Sumatra Province, with a focus on financial ratio analysis and the impact of autonomy. Primary and secondary data were used, involving in-depth interviews and document analysis. Regional financial performance is evaluated with the efficiency ratio, measuring the cost of revenue. There were fluctuations in performance during 2019-2021, with efficient provincial finances in 2019 and 2020, but a decline in 2021. The financial independence ratio measures dependence on local revenue. South Sumatra Province has "medium" independence. The degree of decentralization ratio assesses financial autonomy, with South Sumatra Province in the medium category. The study also pays attention to the effectiveness of local revenue and the level of dependency. Revenue effectiveness fluctuates, while regional dependence is high. Financial performance is influenced by policy, economics and regulations. Improvement efforts in efficiency, independence, degree of decentralization, effectiveness, and dependability are recommended. The implications of this research are important for regional government financial management, increasing efficiency and independence, as well as maintaining stability in autonomy. Regional and central government coordination and community participation need to be improved. Recommendations include considering the impact of policies on efficiency and balance, evaluating revenue management regulations, and regulatory support for efficiency and independence. Increase independence through a degree of decentralization, genuine income, and overcoming barriers. ABSTRAKPenelitian ini menganalisis kinerja dan pengelolaan keuangan di Provinsi Sumatera Selatan, dengan fokus pada analisis rasio keuangan dan dampak otonomi. Data primer dan sekunder digunakan, melibatkan wawancara mendalam dan analisis dokumen. Kinerja keuangan daerah dievaluasi dengan rasio efisiensi, mengukur biaya pendapatan. Terjadi fluktuasi kinerja selama 2019-2021, dengan keuangan provinsi efisien di tahun 2019 dan 2020, tetapi penurunan di tahun 2021. Rasio kemandirian keuangan mengukur ketergantungan pada pendapatan asli daerah. Provinsi Sumatera Selatan memiliki kemandirian "sedang". Rasio derajat desentralisasi menilai otonomi keuangan, dengan Provinsi Sumatera Selatan dalam kategori sedang. Studi juga memperhatikan efektivitas pendapatan asli daerah dan tingkat ketergantungan. Efektivitas pendapatan fluktuatif, sedangkan ketergantungan daerah tinggi. Kinerja keuangan dipengaruhi oleh kebijakan, ekonomi, dan regulasi. Upaya perbaikan di efisiensi, kemandirian, derajat desentralisasi, efektivitas, dan ketergantungan dianjurkan. Implikasi penelitian ini penting bagi pengelolaan keuangan pemerintah daerah, meningkatkan efisiensi dan kemandirian, serta menjaga stabilitas dalam otonomi. Koordinasi pemerintah daerah dan pusat serta partisipasi masyarakat perlu ditingkatkan. Rekomendasi termasuk mempertimbangkan dampak kebijakan terhadap efisiensi dan keseimbangan, evaluasi regulasi pengelolaan pendapatan, dan dukungan regulasi bagi efisiensi dan kemandirian. Meningkatkan kemandirian melalui derajat desentralisasi, pendapatan asli, dan mengatasi hambatan.